Hydrogel with antibacterial, antioxidant and hemostatic functions as well as preparation method and application thereof

By combining natural polymer materials, tannin and okra extracts, and preparing hydrogels using UV-crosslinking technology, the problem that existing hydrogel materials cannot achieve antibacterial, antioxidant and hemostasis functions at the same time, achieving efficient healing of infectious wounds and simplifying the treatment process.

CN119499436APending Publication Date: 2025-02-25THE SECOND AFFILIATED HOSPITAL ARMY MEDICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411715902.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing hydrogel materials have insufficient functional conditions and cannot effectively realize antibacterial, antioxidant and hemostasis functions at the same time, affecting the healing of infectious wounds.

Method used

Using a combination of natural polymer materials, tannin acid and okra extract, hydrogels with three-dimensional network structure were prepared through UV-crosslinking technology to achieve antibacterial, antioxidant and hemostatic functions.

Benefits of technology

The hydrogel significantly improves the healing quality of infectious wounds, reduces inflammatory responses, simplifies the treatment process, and has good plasticity and adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499436A_ABST
    Figure CN119499436A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrogel with antibacterial, antioxidant and hemostatic functions, which comprises the following components in percentage by mass: 4% of natural polymer material, 1.25-5% of tannic acid, 0.25-2% of okra and the balance of solvent. According to the hydrogel disclosed by the invention, through specific raw material selection and a preparation process, the comprehensive performance of the hydrogel in the aspects of antibiosis, antioxidation and hemostasis is improved; meanwhile, the hydrogel is prepared from natural components, is non-toxic and harmless and is easy to degrade, the preparation process is simple and controllable, the cost is relatively low, and large-scale production is easy to realize. In addition, the hydrogel has good plasticity and adhesion, can be tightly attached to the surface of a wound, and provides continuous and effective treatment for the wound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials, and specifically relates to a hydrogel with antibacterial, anti-oxidant and hemostatic functions, a preparation method thereof, and application of the hydrogel in healing of infectious wounds. Background Art

[0002] In the field of biomedical materials, hydrogels, as an important wound dressing, play an important role in wound treatment due to their good biocompatibility, moisture retention and absorbability. In recent years, with the continuous development of materials science, hydrogels with special functions have gradually become a research hotspot. Among them, hydrogels with antibacterial, antioxidant and hemostatic functions have shown great application potential in the treatment of infectious wound healing.

[0003] However, the hydrogel materials in the prior art still have some deficiencies in functionality. For example, although some hydrogels have certain antibacterial capabilities, they often have poor antioxidant properties and cannot effectively remove reactive oxygen species (ROS) at the wound site, thereby being unable to effectively reduce inflammatory responses and affecting wound healing. In addition, although some hydrogels have good hemostatic effects, their antibacterial properties are limited and cannot effectively resist wound infection. Therefore, the development of a hydrogel that simultaneously has antibacterial, antioxidant and hemostatic functions has become a problem to be solved in the current field of biomedical materials technology.

[0004] At present, some relevant patents and literature have reported hydrogel materials with similar functions. For example, [DOI: 10.1002 / adhm.202102791] (Adv. Healthcare Mater) reported a bionic multifunctional black phosphorus hydrogel with certain antibacterial and antioxidant properties. However, the hemostatic effect of this hydrogel is not ideal, and its preparation process is relatively complicated and costly. In addition, [DOI: 10.1002 / advs.202303651] (Advanced Science journal) has also developed an antibacterial hemostatic hydrogel, but the product still needs to be improved in terms of antioxidant properties. Summary of the invention

[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the main purpose of the present invention is to provide a hydrogel with antibacterial, antioxidant and hemostatic functions and a preparation method thereof, which can more effectively promote the healing of infected wounds, reduce inflammatory reactions, improve the quality of healing, and simplify the treatment process.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A hydrogel with antibacterial, anti-oxidation and hemostatic functions comprises, by mass volume fraction, 4% of the natural polymer material, 1.25-5% of tannic acid, 0.25-2% of okra, and the remainder being a solvent.

[0008] In some specific embodiments, the natural polymer material includes one or more of gelatin, chitosan, sodium alginate, collagen, hyaluronic acid, and chondroitin sulfate.

[0009] In certain specific embodiments, the natural polymer material is hyaluronic acid, and the hyaluronic acid is methacrylic anhydride hyaluronic acid; and the solvent is a lithium phenyl-2,4,6-trimethylbenzoylphosphinate solution with a mass concentration of 0.5%.

[0010] The present invention also provides a method for preparing the aforementioned hydrogel having antibacterial, antioxidant and hemostatic functions, comprising the following steps:

[0011] 1) dissolving a natural polymer material in a lithium phenyl-2,4,6-trimethylbenzoylphosphinate solution to form a natural polymer hydrogel precursor solution;

[0012] 2) dissolving tannic acid and dispersing it into the natural polymer hydrogel precursor solution in step 1) to obtain a natural polymer@tannic acid composite solution;

[0013] 3) adding okra to the natural polymer @ tannic acid composite solution in step 2) and stirring evenly to obtain a natural polymer @ tannic acid-okra solution;

[0014] 4) Using UV-crosslinking technology, the natural polymer @ tannic acid-okra solution in step 3) is crosslinked and cured in a mold to obtain a hydrogel with a three-dimensional network structure, that is, a hydrogel with antibacterial, antioxidant and hemostatic functions.

[0015] Furthermore, a method for preparing a hydrogel having antibacterial, antioxidant and hemostatic functions comprises the following steps: wherein the natural polymer material used is methacrylic anhydride hyaluronic acid;

[0016] 1) dissolving HAMA in a lithium phenyl-2,4,6-trimethylbenzoylphosphinate solution to form a HAMA hydrogel precursor solution;

[0017] 2) dissolving tannic acid and dispersing it into the HAMA hydrogel precursor solution in step 1) to obtain a HA@TA composite solution;

[0018] 3) adding okra to the HA@TA composite solution in step 2) and stirring evenly to obtain a HA@TA-Okra solution;

[0019] 4) Using UV-crosslinking technology, the HA@TA-Okra solution in step 3) is crosslinked and cured in a mold to obtain a hydrogel with a three-dimensional network structure, that is, a hydrogel with antibacterial, antioxidant and hemostatic functions.

[0020] In certain embodiments, the preparation method of the hydrogel having antibacterial, antioxidant and hemostatic functions is:

[0021] First, 0.4 g of HAMA solid sample was dissolved in 1 ml of 0.5% lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP) solution and stirred thoroughly to prepare a HAMA hydrogel precursor solution with a concentration of 4% (w / v%);

[0022] Tannic acid (TA) was dissolved and evenly dispersed into the HAMA hydrogel precursor solution with a concentration of 4 w / v% according to the mass ratio (specifically 1.25, 2.5, and 5 w / v%). Three HA@TA hydrogel precursor solutions with different TA contents were successfully prepared and named HA@TA1.25, HA@TA2.5, and HA@TA5.

[0023] On this basis, okra was further incorporated into 4w / v% HAMA hydrogel containing 2.5w / v% TA in different proportions (0.25, 0.5, 1 and 2w / v%) to obtain a series of hydrogel precursors: HA@TA-Okra0.25, HA@TA-Okra0.5, HA@TA-Okra1 and HA@TA-Okra2.

[0024] Finally, the aforementioned different types of hydrogels were successfully solidified using efficient UV cross-linking technology (wavelength of 405 nm).

[0025] The present invention also aims to provide a use of the aforementioned hydrogel having antibacterial, antioxidant and hemostatic functions in the preparation of healing drugs for treating infected wounds.

[0026] In certain embodiments, the hydrogel is capable of stopping bleeding and promoting wound repair.

[0027] The present invention also aims to provide an application of the aforementioned hydrogel having antibacterial, antioxidant and hemostatic functions in the field of tissue engineering and regenerative medicine.

[0028] Compared with the prior art, the present invention has at least the following advantages:

[0029] The present invention provides a hydrogel with antibacterial, antioxidant and hemostatic functions to solve the problems currently faced in the healing treatment of infectious wounds; through specific raw material selection and preparation process, the comprehensive performance of the hydrogel in antibacterial, antioxidant and hemostatic aspects is improved, providing a new solution for the healing treatment of infectious wounds.

[0030] The HA@TA-Okra hydrogel of the present invention is prepared from natural ingredients, is non-toxic and harmless and is easily degradable. Its preparation process is simple and controllable, the cost is relatively low, and it is easy to achieve large-scale production. In addition, the hydrogel has good plasticity and adhesion, can fit closely to the wound surface, and provide continuous and effective treatment for the wound. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.

[0032] Figure 1 Characterization of the HA@TA-Okra hydrogel (HA@TA2.5-Okra0.5) provided in Example 1 of the present invention; wherein (A) SEM image of the hydrogel; (B) pore size analysis of the hydrogel; (C) box plot statistics of the hydrogel contact angle; (D) HAMA and HA@TA-Okra hydrogel formed by ultraviolet irradiation (405nm, 30s); (E) hydrogel contact angle; (F) injectability evaluation of the HA@TA-Okra hydrogel; (G) FTIR spectra of HAMA, HA@TA, HA@Okra and HA@TA-Okra; (H) hydrogel degradation rate; (I) hydrogel swelling ratio;

[0033] Figure 2 The cytotoxicity and in vitro cell migration behavior of different hydrogels provided by the present invention: (A) Cytotoxicity of L929 cells co-cultured with hydrogel extracts containing different concentrations of TA for 1, 3, and 5 days; (B) Determination of DPPH scavenging rate of HAMA and HA@TA1.25 / 2.5 / 5 hydrogels; (C) Cytotoxicity of L929 cells co-cultured with hydrogel extracts for 1, 3, and 5 days; (D) EdU fluorescence image; (E) Migration ability of L929 cells after co-culture with different hydrogel extracts; (F) EdU statistical chart; (G) Quantification of cut edge closure rate among 31 groups at 12H and (H) 24H (*P<0.05, **P<0.01, ***P<0.001);

[0034] Figure 3Determination of the in vitro antibacterial activity of the HA@TA-Okra hydrogel (HA@TA2.5-Okra0.5) provided in Example 1 against Escherichia coli and Staphylococcus aureus: (A) bacterial plate count; (B) live / dead staining of Escherichia coli and Staphylococcus aureus treated with different hydrogels (green: live bacteria, red: dead bacteria); statistics of the antibacterial rates of different hydrogels against (C) Escherichia coli and (D) Staphylococcus aureus (**p<0.01, **p<0.001);

[0035] Figure 4 In vitro antioxidant and anti-inflammatory activities of the HA@TA-Okra hydrogel (HA@TA2.5-Okra0.5) provided in Example 1 of the present invention: (A) determination of DPPH clearance rate of different hydrogels; (B) represents ROS fluorescence intensity; (C) detection of intracellular ROS under different hydrogels (green fluorescence represents ROS); quantitative analysis of the secretion of (D) TNF-α and (E) IL-6 (F) IL10 by RAW264.7 cells of different samples (*p<0.05, **p<0.01, ***p<0.001);

[0036] Figure 5 The blood biocompatibility and coagulation properties of the HA@TA-Okra hydrogel (HA@TA2.5-Okra0.5) provided in Example 1 of the present invention: (A) hemolysis test photos of different hydrogels; (B) hemolysis rate; (C) blood absorption photos of gauze and different hydrogels in contact with blood and soaked in PBS for 1 minute; (D) BCI statistical results; (E) SEM images of blood cells and platelets adhesion on different hydrogels (*p<0.05, **p<0.01, ***p<0.001);

[0037] Figure 6 In vivo hemostatic performance of the HA@TA-Okra hydrogel (HA@TA2.5-Okra0.5) provided in Example 1 of the present invention: photos of hemostatic performance of different hydrogels in (A) liver incision and (B) tail amputation models; bleeding volume of different hydrogels in (C) liver incision and (D) tail amputation models (**p<0.01, **p<0.001);

[0038] Figure 7The HA@TA-Okra hydrogel (HA@TA2.5-Okra0.5) provided in Example 1 of the present invention promotes the healing of full-thickness skin defect wounds: wherein (A) representative photos of the wounds of each group after 0, 3, 7, 10, and 14 days of treatment; (B) quantification of the wound area of ​​each group; (C) wound treatment modes of different groups; H&E and Masson staining images of the wound defects of each group on the 7th day (D) and the 14th day (E); (F) statistics of skin thickness; (G) statistics of 37 granulation tissue thickness; (H) statistics of collagen percentage (*p<0.05, **p<0.01, ***p<0.001);

[0039] Figure 8 The HA@TA-Okra hydrogel (HA@TA2.5-Okra0.5) provided in Example 1 of the present invention promotes healing of infected wounds: (A) pictures of the infected model wound after 0, 3, 7, 10, and 14 days of treatment; (B) quantification of the wound area of ​​each group; (C) photos of Staphylococcus aureus in the infected skin on the 3rd day; (D) colony count statistics; (E) H&E and (F) Masson staining images of 39 groups of wound defects on the 7th and 14th days; (G) skin thickness statistics; (H) granulation tissue thickness statistics; (I) collagen percentage statistics (*p<0.05, **p<0.01, ***p<0.001);. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but it should not be understood as limiting the scope of protection of the present invention. Any equivalent changes in form made based on the concept of the present invention should be regarded as the scope of the present invention.

[0041] The present invention provides a general and / or specific description of the materials and test methods used in the experiment. The test methods or test methods involved are all conventional methods unless otherwise specified; the reagents or instruments used are all conventional products available on the market, prepared or used in a conventional manner, unless the manufacturer is specified.

[0042] In the following examples, the methacrylic anhydride hyaluronic acid (HAMA) used can be purchased through commercial channels; its role in the present application is to serve as the main material of the hydrogel, provide good biocompatibility and degradability, and simulate the natural extracellular matrix (ECM) structure to promote cell attachment and proliferation;

[0043] The tannic acid (TA) used is a natural plant extract; its role in the present application is to enhance the antioxidant and antibacterial properties of the hydrogel, provide hydrogen bonding interactions through its polyphenol structure, and stabilize the hydrogel structure;

[0044] The okra extract used was purchased from Sichuan Weikeqi Biotechnology Co., Ltd.; its function is to further enhance the antioxidant and coagulation properties of the hydrogel, which may be achieved by activating platelets and promoting the release of coagulation factors.

[0045] The test methods used in the following embodiments include:

[0046] The physical properties and functional characteristics are reflected by testing the main properties of each test sample respectively; the main properties tested in this application include physicochemical properties and functional properties.

[0047] 1) Electron microscope test;

[0048] The microstructure of HAMA hydrogel and HA@TA-Okra hydrogel was observed using a scanning electron microscope (SEM). The hydrogel was prepared into a size of 3mm×3mm, and the sample surface was ensured to be clean and flawless. The hydrogel was fixed on a metal frame with conductive glue. After being properly fixed, it was placed in the vacuum chamber of the gold spraying equipment, sprayed with gold for 60 seconds under vacuum conditions, and observed at an accelerating voltage of 10kV. The pore diameter was randomly measured using Image J software to quantitatively analyze the pore structure of the two hydrogels.

[0049] 2) Injectability test

[0050] Place the HA@TA-Okra hydrogel precursor solution in a 1 ml syringe. Extrude the hydrogel solution through a standard needle. During this process, observe and record the injection smoothness and morphology retention ability of the hydrogel;

[0051] 3) Hydrophilicity test

[0052] The hydrophilic properties of HA@TA-Okra hydrogel were tested using a contact angle tester. The experiment was conducted at standard room temperature. First, the HA@TA-Okra hydrogel sample was prepared into a rectangular shape of 50mm×10mm×10mm, then it was firmly attached to a glass slide using double-sided tape, and the glass slide was placed on the test platform of the contact angle tester. In order to evaluate its hydrophilicity, 5 microliters of deionized water were used as the test droplet. The droplet was accurately added to the hydrogel surface at a constant rate (5 microliters / second). The shape of the droplet was observed through the microscope of the contact angle tester, and the image of the droplet was recorded using an image acquisition system.

[0053] 4) Chemical property analysis

[0054] The chemical composition of HA@TA-Okra hydrogel was detected by Fourier transform infrared spectroscopy (FTIR). The hydrogel sample was first dried to constant weight using a freeze dryer under standard room temperature conditions. Subsequently, the scanning range of the FTIR instrument was precisely set to 4000 to 400 cm-1.

[0055] 5). Degradability test

[0056] In order to comprehensively evaluate the in vitro degradation performance of HA@TA-Okra hydrogel, we prepared HA@TA-Okra hydrogel into a standardized cylindrical shape with a bottom diameter of 8 mm and a height of 5 mm. First, the initial dry weight of HA@TA-Okra hydrogel was recorded (marked as Wo). Subsequently, the hydrogel sample was placed in phosphate buffered saline (PBS) and incubated at a constant temperature of 37°C. At continuous time points from 0 to 25 days, HA@TA-Okra hydrogel samples were regularly removed from PBS, and after freeze-drying, their dry weight after degradation (marked as Wt) was recorded in detail. The degradation rate of the sample was calculated by the equation: Degradation rate (%) = (W0–Wt) / W0×100%;

[0057] 6). Swelling test

[0058] In order to comprehensively evaluate the in vitro swelling properties of HA@TA-Okra hydrogel, HA@TA-Okra hydrogel was prepared into a standardized cylindrical shape with a bottom diameter of 8 mm and a height of 5 mm. First, the initial dry weight (Wo) of the hydrogel was recorded. Subsequently, the hydrogel was immersed in a phosphate buffer solution (PBS) at 37°C for 24 hours to simulate the in vivo environment. After the immersion, the excess water on the surface of the hydrogel was carefully removed, and its wet weight (Ww) was immediately weighed. The swelling rate of the sample was calculated by the equation: Swelling rate (%) = W0–Wt) / W0×100%;

[0059] 7) In vitro biocompatibility testing

[0060] The experiment was conducted using L929 cells as model cells: first, the frozen L929 cells were thawed and revived, and then the cells were transferred to DMEM culture medium (containing 10% fetal bovine serum and 1% double antibody), and the residual cryopreservation solution was removed by centrifugation. Subsequently, the cells were placed in a cell culture incubator, and fresh culture medium was replaced every 48 hours; after the cells were successfully passaged to the second generation, the cell inoculation operation was performed.

[0061] HAMA and HA@TA hydrogels with different concentrations were completely immersed in the whole culture medium at a concentration of 0.1 g / ml for 24 hours. Subsequently, the cytotoxicity level of these extracts was evaluated using the CCK-8 cell activity assay kit. L929 cells were cultured at 1×10^ 4The cells were evenly inoculated in a 24-well culture plate at a density of 100 cells / cm2, and the pre-treated hydrogel extracts of each group were added to each well, and cultured in a constant temperature incubator at 37°C and 5% CO2. On the 1st, 3rd, and 5th days of culture, fresh complete medium containing 10% CCK-8 reagent was added to each well at a fixed time point, and incubation continued at 37°C. Finally, the absorbance value of each well was measured at a wavelength of 450 nanometers by an ELISA reader.

[0062] 8) Antioxidant test

[0063] The antioxidant capacity of HAMA and HA@TA (including HA@TA1.25, HA@TA2.5, and HA@TA5) hydrogels with different tannic acid concentrations was detected through the DPPH free radical scavenging experiment. First, the above four hydrogels were refined separately using a homogenizer. Subsequently, the hydrogel samples of each group after refinement were added to an anhydrous ethanol solution containing DPPH and incubated in the dark for 30 minutes. In this process, vitamin C was used as a positive control. After the reaction, the absorbance of each solution was measured at a wavelength of 515nm using an enzyme reader. Among them, Ao represents the initial absorbance of the DPPH solution at 515nm when no hydrogel is added; A1 represents the absorbance of the DPPH solution at the same wavelength after the addition of the hydrogel. Based on the above data, the antioxidant activity of the hydrogel is calculated by the equation: Antioxidant activity (%) = (A1-A0) / A0×100%;

[0064] 9) Antibacterial performance testing

[0065] Experiments were conducted using Escherichia coli and Staphylococcus aureus as model bacteria: first, the strains of Escherichia coli and Staphylococcus aureus were activated, then the strains were transferred to nutrient broth medium and cultured in a shaking incubator at 37°C. When the bacteria reached the desired growth stage, they were separated from the culture medium using sterile centrifuge tubes to collect the bacteria.

[0066] The antibacterial ability of HAMA and HA@TA hydrogels with different tannic acid concentrations (including HA@TA1.25, HA@TA2.5, and HA@TA5) was evaluated by the drop plate method in the plate counting experiment. First, under sterile conditions, 100 μL of 1×10^ 5CFU / mL of bacterial solution (Escherichia coli and Staphylococcus aureus) was evenly dripped onto the above four hydrogels with a mass of 35 mg. Subsequently, each group of hydrogels was placed in an incubator at 37°C and incubated for 6 hours. After the incubation, the bacteria on the hydrogel were eluted with sterile phosphate buffered saline (PBS), and 100 μL of the washing solution was evenly applied to the agar plate. Then, the agar plate was placed in a bacterial incubator at 37°C and incubated for 24 hours. The colony count of the blank control group was set to B0, and the colony count of the experimental group (i.e., the group with the sample added) was set to B1. The antibacterial rate is calculated by the following formula: Antibacterial activity (%) = (B0-B1) / B0×100%;

[0067] 10) Effects on cell proliferation

[0068] The overall proliferation of cells treated with hydrogels in each group was quantitatively evaluated using the EdU cell proliferation kit. First, under sterile conditions, 100 μl of L929 cell suspension was inoculated into each well of a 24-well cell culture plate. The cell density of the suspension was adjusted to 2 × 10^ 5 cells / ml. Subsequently, different types of hydrogel extracts were introduced into each well to stimulate the proliferation response of L929 cells. L929 cells were labeled with EdU. L929 cells were fixed to maintain their morphology and structure, and the fixed cells were systematically stained according to the staining scheme provided by the kit, including incubation with Apollo staining reaction solution and addition of DNA staining solution. Finally, the stained L929 cells were carefully observed and photographed using an inverted microscope.

[0069] 11) Effects on cell migration

[0070] The ability of each group of hydrogels in promoting L929 cell migration was tested by scratch test. First, 1×10^ 4L929 cells were inoculated at a density of 10 cells and cultured under appropriate conditions until the cell fusion rate reached about 90% and a uniform cell monolayer was formed. Subsequently, a sterile 200 μl pipette tip was used to accurately scratch a clear and cell-free trace at the bottom of the well plate. After the scratch was completed, the original culture medium was gently discarded, and the well plate was washed with phosphate buffered saline (PBS) to completely remove non-adherent cells and cell debris. Then, HAMA, HA@TA, HA@Okra and HA@TA-Okra hydrogel extracts were added to each well. After incubation in a cell culture incubator for 0 hours (A0, i.e., observation immediately after scratching), 12 hours (As, i.e., observation 24 hours after scratching) and 24 hours (At, i.e., observation 24 hours after scratching), the cells were stained with calcein for 5 minutes. Finally, the migration of L929 was carefully observed and photographed using a fluorescent inverted microscope. The unhealed area after scratching was quantitatively analyzed by ImageJ software, and the scratch healing rate (%) was calculated using the formula. The healing rate calculation formula is: healing rate (%) = (A0-As) / A0×100% and (A0-At) / A0×100%;

[0071] 12) Antibacterial performance testing

[0072] (1) The method is the same as before, activating Escherichia coli and Staphylococcus aureus. Using the drop plate method in the plate counting experiment, the hydrogel flushing solution containing each group is evenly spread on the agar plate under a sterile environment. The colony count of the blank control group is set as B0, and the colony count of the experimental group (i.e., the group with different hydrogels added) is set as B1. The antibacterial rate of the sample is calculated by the following formula: Antibacterial activity (%) = (B0-B1) / B0×100%;

[0073] (2) The method was the same as before, and Escherichia coli and Staphylococcus aureus were activated. The live / dead staining kit was used for detection. First, each group of hydrogel samples was completely immersed in 10 mL of 1×10^ 5 CFU / mL test tube bacterial suspension to ensure that the hydrogel sample is in full contact with the bacteria. Subsequently, it was incubated in a shake flask for 24 hours. After the incubation, the suspension containing the bacteria was collected and centrifuged (speed was 5000rpm, centrifugation time was 10 minutes) to collect the bacteria. The isolated bacterial samples were stained using a live / dead staining kit. The staining process was carried out at room temperature (dark environment). After staining, 5μl of the stained bacterial suspension was transferred to a slide and observed under a fluorescence microscope.

[0074] 13) Reactive oxygen species (ROS) scavenging assay

[0075] By 2',7'-dichlorofluorescein diacetate (DCFH-DA) labeling, the ROS levels in RAW264.7 cells to which each group of hydrogel extracts were added were measured under lipopolysaccharide (LPS) stimulation conditions. RAW264.7 cells were cultured using conventional techniques in the art. Labeling with DCFH-DA enabled intracellular ROS to be converted into substances with fluorescent properties. After RAW264.7 cells were cultured to an appropriate density, they were divided into two groups for treatment. One group of cells was stimulated with LPS to simulate an inflammatory response environment; while the other group of cells was stimulated with LPS and four different hydrogel extracts were added. The effect of hydrogels on ROS levels in RAW264.7 cells was observed using a fluorescence microscope.

[0076] 14) Regulation of cellular inflammatory response

[0077] The concentrations of key inflammatory factors, tumor necrosis factor TNF-α, interleukin IL-6, and anti-inflammatory factor IL-10, were quantitatively detected by enzyme-linked immunosorbent assay (ELISA). RAW264.7 cells were cultured and cultured at 1×10 5 The cells were uniformly seeded in a 24-well plate at a density of 100 cells / well. Subsequently, the cells were co-incubated with the hydrogel extracts of each group for 24 hours. After the incubation, the supernatant was collected and the dead cells and cell debris were removed by centrifugation. Subsequently, the concentrations of TNF-α, IL-6 and IL-10 were accurately determined using ELISA kits.

[0078] 15) In vitro blood compatibility test

[0079] (1) Hemolytic performance test

[0080] The hemolytic properties of each group of hydrogels were tested using New Zealand sheep blood. First, the mixed solution of fresh sheep blood and 3.8% sodium citrate (volume ratio of 1:9) was centrifuged (2000rpm, 5min) to effectively separate the red blood cells, and the red blood cells were prepared into a red blood cell suspension with a volume fraction of 5% using physiological saline. Take 0.2g of each group of hydrogels and soak them in 10ml of phosphate buffered saline (PBS) for 48h to obtain extracts of different groups of hydrogels. Then, take out 0.5ml from the extract and add it to a 1.5ml centrifuge tube containing 0.5ml red blood cell suspension for 1 hour of incubation. After the incubation, centrifuge again (2000rpm, 5min) to separate the supernatant. Use an enzyme marker to measure the absorbance value of the supernatant at a wavelength of 540. At the same time, two groups of control experiments were set up: one group used PBS as a negative control (Anc), and the other group used deionized water as a positive control (Apc), and the supernatant (At) was separated from 1 ml of the suspension by centrifugation. The hemolysis rate calculation formula is: hemolysis rate (%) = (At-Anc) / (Apc-Anc) × 100%;

[0081] (2) Blood coagulation index (BCI)

[0082] The blood coagulation performance (BCI) of each group of hydrogels was evaluated by detecting the effects of each group of hydrogels and gauze on blood coagulation. First, each group of hydrogel samples and gauze with a mass of 35 mg were selected, and 100 μL of New Zealand sheep whole blood was dripped onto each of them. Subsequently, it was incubated at a constant temperature of 37°C for 10 minutes. After the incubation, 10 μL of 0.2M calcium chloride (CaCl2) solution and 10 ml PBS solution were added to each sample. The absorbance value of the PBS solution after blood diffusion was measured at a wavelength of 540 nanometers using a spectrophotometer, which was recorded as As. At the same time, the absorbance value after only whole blood was added to PBS was measured as a negative control, recorded as Ac. The formula for calculating the coagulation rate is: Coagulation rate (%) = As / Ac×100%;

[0083] (3) Platelet adhesion performance test

[0084] Blood cells and platelets were observed by SEM to detect the effects of each group of hydrogels on the adhesion properties of blood cells and platelets. First, each group of hydrogel samples with a mass of 35 mg were selected, placed in a 24-well plate, and a whole blood sponge containing 10% sodium citrate was added. After incubation at a constant temperature of 37°C for 1 hour, all samples were washed 3 times with PBS. All samples were fixed with 4% paraformaldehyde for 2 hours. Subsequently, the samples were dehydrated using an ethanol gradient and observed under a scanning electron microscope.

[0085] 16) In vivo hemostatic effect detection

[0086] (1) Detection of hemostasis effect of liver incision

[0087] The hemostatic effect of each group of hydrogels was tested by the SD rat liver incision model. Male SD rats (weight range 200-250 grams) were selected, and the experimental protocol approved by the Ethics Committee of the Army Medical University (AMUWEC20235104) was strictly followed. An untreated control group was also set up. First, the SD rats were anesthetized with sodium pentobarbital, and the fur on the abdomen of the rats was shaved clean and disinfected. A 3 cm incision was made on the left liver lobe of the rat using a scalpel, and bleeding was allowed for 5 seconds. Subsequently, each group of pre-weighed (35 mg) hydrogels was gently covered on the wound, and slight pressure was applied to achieve a hemostatic effect. Record the bleeding time and amount of bleeding.

[0088] (2) Testing of the hemostatic effect of tail cutting

[0089] Use surgical scissors to cut the posterior third of the rat's tail;

[0090] 17) In vivo wound healing assay

[0091] (1) Full-thickness skin defect model on the back of SD rats

[0092] The effect of each group of hydrogels on wound healing was detected by using a full-thickness skin defect model on the back of SD rats. The specific method is as follows: SD rats (200-250g, male) were selected and randomly divided into 4 groups (n=4), namely the control group (untreated), gauze group, HAMA hydrogel group and HA@TA-Okra hydrogel group. After all rats were anesthetized with sodium pentobarbital and shaved on the back, four wounds with a diameter of about 15mm and a depth of about 2mm were made on their backs using sterile instruments (the four wounds did not interfere with each other). Subsequently, the control group kept the wound untreated; the gauze group covered the wound with gauze; the HAMA hydrogel group and the HA@TA-Okra hydrogel group were evenly coated with 200μL of the corresponding hydrogel until the wound surface was flat. The wound surface was photographed on days 0, 3, 7, 10, and 14, and the changes in the wound area were accurately measured and recorded using Image J software.

[0093] (2) SD rat back infected full-thickness skin defect model

[0094] The same bacterial activation method was used to activate Staphylococcus aureus. Staphylococcus aureus (100 μL, 106 CFU mL-1) was inoculated on each wound surface in the SD rat back full-thickness skin defect model. The rest was the same as the SD rat back full-thickness skin defect model.

[0095] Example 1: Preparation of hydrogel

[0096] This embodiment provides a method for preparing a hydrogel having antibacterial, antioxidant and hemostatic functions, which comprises the following steps:

[0097] 1) dissolving methacrylic anhydride hyaluronic acid (HAMA) in 1 ml of 0.5% lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP) solution, and stirring well to prepare methacrylic anhydride hyaluronic acid (HAMA) hydrogel precursor solution;

[0098] 2) dissolving tannic acid (TA) in an appropriate amount of solvent to form a tannic acid (TA) solution; and uniformly dispersing the tannic acid (TA) solution into the methacrylic anhydride hyaluronic acid (HAMA) hydrogel precursor solution obtained in step 1) to obtain a HA@TA composite solution;

[0099] 3) Adding the okra extract to the HA@TA composite solution obtained in step 2) and mixing them thoroughly to form a HA@TA-Okra hydrogel solution.

[0100] The HA@TA-Okra hydrogel solution includes the following components in terms of mass percentage (w / v%):

[0101] Methacrylate anhydride hyaluronic acid (HAMA): 4%, tannic acid (TA): 2.5%, okra extract: 0.5% (HA@TA2.5-Okra0.5).

[0102] The present application also adopts the same preparation method as that of the embodiment to prepare composite solutions with mass volume fractions of tannic acid of 1.25%, 2.5% and 5%, referred to as HA@TA1.25, HA@TA2.5 and HA@TA5.

[0103] Example 2

[0104] This embodiment provides a method for preparing a hydrogel having antibacterial, antioxidant and hemostatic functions, which comprises the following steps:

[0105] 1) dissolving methacrylic anhydride hyaluronic acid (HAMA) in 1 ml of 0.5% lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP) solution, and stirring well to prepare methacrylic anhydride hyaluronic acid (HAMA) hydrogel precursor solution;

[0106] 2) dissolving tannic acid (TA) in an appropriate amount of solvent to form a tannic acid (TA) solution; and uniformly dispersing the tannic acid (TA) solution into the methacrylic anhydride hyaluronic acid (HAMA) hydrogel precursor solution obtained in step 1) to obtain a HA@TA composite solution;

[0107] 3) Adding the okra extract to the HA@TA composite solution obtained in step 2) and mixing them thoroughly to form a HA@TA-Okra hydrogel solution.

[0108] The HA@TA-Okra hydrogel solution comprises the following components in terms of mass percentage (w / v%):

[0109] Methacrylic anhydride hyaluronic acid (HAMA): 4%, tannic acid (TA): 5%, okra extract: 1% (HA@TA5-Okra1).

[0110] The present application also adopts the same preparation method as Example 1 to prepare hydrogels such as HA@TA2.5-Okra0.25 (abbreviated as HA@TA-Okra0.25), HA@TA2.5-Okra0.5 (abbreviated as HA@TA-Okra0.5), HA@TA2.5-Okra1 (abbreviated as HA@TA-Okra1) and HA@TA2.5-Okra2 (abbreviated as HA@TA-Okra2).

[0111] Comparative Example 1

[0112] This comparative example provides a method for preparing a hydrogel having antibacterial, antioxidant and hemostatic functions, which is basically the same as Example 1, except that tannic acid is not added, and specifically comprises the following steps:

[0113] 1) dissolving methacrylic anhydride hyaluronic acid (HAMA) in 1 ml of 0.5% lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP) solution, and stirring well to prepare methacrylic anhydride hyaluronic acid (HAMA) hydrogel precursor solution;

[0114] 3) Adding the okra extract to the methacrylic anhydride hyaluronic acid (HAMA) hydrogel precursor solution obtained in step 1), and mixing them thoroughly to form a HA@Okra hydrogel solution.

[0115] The HA@TA-Okra hydrogel solution comprises the following components by mass percentage: methacrylic anhydride hyaluronic acid (HAMA): 4% and okra extract: 0.5%.

[0116] Performance test example:

[0117] 1. Characterization of physical and chemical properties

[0118] This test example takes Example 1 (HA@TA2.5-Okra0.5) as an example to characterize the physical and chemical properties of the prepared HA@TA-Okra hydrogel solution, specifically:

[0119] 1) Electron microscope test

[0120] In the present invention, the microscopic morphology and pore length distribution of HAMA hydrogel and HA@TA-Okra hydrogel are as follows: Figure 1 A and 1B. Both exhibit uniformly distributed porous structures with pore sizes of approximately 188±31μm (HAMA) and 150±37μm (HA@TA-Okra), respectively.

[0121] 2) Injectability test

[0122] In the present invention, it was found that both HAMA and HA@TA-Okra hydrogels have excellent injectability, which enables them to flexibly adapt to the repair needs of wounds of various shapes, such as Figure 1 The different shapes of HA@TA-Okra hydrogels are shown in Figure F. By precisely controlling the injection process, these hydrogels can be accurately filled into the target area and then solidified to form a stable structure; the hydrogels formed by ultraviolet radiation (405nm, 30s) of HAMA and HA@TA-Okra hydrogels are shown in Figure 3. Figure 1 D;

[0123] 3. Hydrophilicity test

[0124] In the present invention, the hydrophilicity of the hydrogel is analyzed using a contact angle tester. Specifically, the contact angle refers to the angle θ between the tangent line of the gas-liquid interface and the solid-liquid boundary line at the intersection of the gas, liquid and solid phases. This angle is a key indicator for measuring the wettability of the material. When θ is less than 90°, the material is considered hydrophilic; and the smaller the θ value, the stronger the hydrophilicity of the material. On the contrary, if θ is greater than 90°, the material is considered hydrophobic. Figure 1 As shown in Figure E, this principle can clearly demonstrate the measurement of contact angle and the criterion for judging hydrophilicity.

[0125] Furthermore, if Figure 1 As shown in C, the experimental results show that both HAMA and HA@TA-Okra hydrogels exhibit extremely significant hydrophilicity, and their contact angles are approximately 1° and 2°, respectively.

[0126] 4) Chemical property analysis

[0127] In the present invention, the chemical composition of the hydrogel was analyzed in detail using Fourier transform infrared spectroscopy (FTIR). Figure 1 G, at 3200-3500cm -1In the wavenumber range, an obvious broad absorption band was observed, which was attributed to the characteristic vibration of the hydroxyl (OH) groups in HAMA, TA and Okra. Spectral analysis further revealed that hydrogen bonding interactions may have formed between HAMA, TA and Okra molecules, resulting in a slight shift of the absorption peak of the hydroxyl stretching vibration mode of HA@TA-Okra to the low frequency direction, accompanied by an increase in the complexity of the peak shape, which directly reflects the formation of a hydrogen bonding network.

[0128] 1700~1750cm -1 In the wavenumber range, a new complex absorption characteristic peak also appeared in the FTIR spectrum, which we believe corresponds to the vibration of the ester bond (C=OOC) inside the HA@TA-Okra hydrogel. Compared with other hydrogels, this absorption peak shows higher complexity, which may be due to the formation of an ester bond structure inside the HA@TA-Okra hydrogel.

[0129] 5) Degradability

[0130] In the present invention, the degradation performance of the hydrogels was studied by the weight changes of each group of hydrogels immersed in PBS. Figure 1 As shown in Figure 3, at the beginning of the experiment (day 5), the degradation rate of all hydrogels reached about 40%. This result strongly supports the view that in the initial stage, partial degradation of hydrogels can create a favorable environment for cell proliferation.

[0131] As the experimental time continued to extend, the degradation rate of the hydrogel gradually slowed down and tended to stabilize after 25 days, with the degradation rate maintained in a relatively constant range of 60% to 80%.

[0132] 6) Swelling

[0133] In the present invention, the swelling properties of the hydrogels were studied by the weight changes of each group of hydrogels immersed in PBS. The ability to absorb body fluids, metabolites and exudates is very important for establishing a microenvironment for tissue repair. Figure 1 As shown in Figure 1, all tested hydrogels exhibited a significant increase in swelling ratio. Swelling equilibrium was reached within approximately 24 h, with swelling ratios ranging from 310% to 335%.

[0134] 2. Functional testing

[0135] 1) Safety evaluation of hydrogels on cells

[0136] This test evaluated the safety of the hydrogel on cells:

[0137] Test materials and test methods:

[0138] In this test example, the hydrogel solutions of Control, HAMA, HA@TA-Okra0.25, HA@TA-Okra0.5, HA@TA-Okra1, and HA@TA-Okra2 were immersed in complete culture medium at a ratio of 0.1 g / mL for 24 hours, and the hydrogel extracts were collected; then, the CCK-8 test was used to evaluate the cytotoxicity of the hydrogels, specifically:

[0139] L929 cells were plated at 1×10 4 The cells were seeded at a density of 100 cells / mL in a 24-well plate and cultured with the hydrogel extracts at 37°C and 5% CO2. At the same time, fresh complete medium containing 10% CCK-8 reagent was added to each well on days 1, 3, and 5. The hydrogels were then incubated in an incubator at 37°C, and the absorbance was measured at 450 nm using a microplate reader (Thermo, USA) to assess compatibility.

[0140] Results and Discussion:

[0141] The biocompatibility characteristics of HA@TA1.25 / 2.5 / 5 hydrogel were systematically evaluated. Figure 2 As shown in A, all groups showed a trend of cell proliferation over time. At the fifth day, the cell proliferation rates of the HA@TA1.25 and HA@TA2.5 groups were maintained at a high level, comparable to the HAMA group (P>0.05). In summary, the hydrogel prepared in this application has excellent biocompatibility. The cell proliferation rate of the HA@TA5 group was slower than that of the HA@TA1.25 and HA@TA2.5 groups (P<0.001), which may be due to the high TA concentration (5%) exceeding the safety threshold that the cells can tolerate.

[0142] 2): Hydrogel has excellent antioxidant properties

[0143] This test evaluated the antioxidant properties of HA@TA-Okra hydrogel solution, specifically:

[0144] Test materials and test methods:

[0145] In this test example, the hydrogel solutions of Positive, HAMA, HA / TA1.25, HA / TA2.5 and HA / TA5 were immersed in complete culture medium at a ratio of 0.1 g / mL for 24 hours, and the hydrogel extracts were collected; then, the CCK-8 test was used to evaluate the cytotoxicity of the hydrogels, specifically:

[0146] L929 cells were plated at 1×10 4The cells were seeded at a density of 100 cells / mL in 24-well plates and cultured with hydrogel extracts at 37°C and 5% CO2. Meanwhile, fresh complete medium containing 10% CCK-8 reagent was added to each well on days 1, 3, and 5. The hydrogels were then incubated in an incubator at 37°C. The antioxidant properties of the hydrogels were determined by their ability to scavenge 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radicals. Following the DPPH assay protocol, vitamin C was used as a positive control and the absorbance was measured on a microplate reader at 515 nm. The antioxidant activity was calculated according to the manufacturer's instructions and expressed as a percentage.

[0147] Results and Discussion:

[0148] In response to the oxidative stress challenge commonly found in infected wound environments, the DPPH free radical scavenging assay was used to quantitatively evaluate the in vitro antioxidant effect of HA@TA1.25 / 2.5 / 5 hydrogel. Figure 2 As shown in Figure B, the DPPH scavenging rate increased significantly with the increase of TA concentration. Specifically, the DPPH scavenging rate of the HA@TA1.25 group was about 73%, while the scavenging efficiency of the HA@TA2.5 and HA@TA5 groups exceeded 80%, which was much better. This finding emphasizes the strong antioxidant potential of the TA polyphenol structure and further confirms that the antioxidant properties of the hydrogel can be effectively enhanced by adjusting the TA concentration. In contrast, the HAMA hydrogel performed poorly in the DPPH scavenging test, with a scavenging rate of only 4%, which is negligible.

[0149] In summary, the rich phenolic hydroxyl structure of tannic acid makes it a highly effective antioxidant that can quickly respond to and neutralize various types of reactive oxygen species (ROS), including DPPH free radicals. Experimental data show that the antioxidant properties of HA@TA-Okra hydrogels are significantly better than those of hydrogels containing only HAMA or okra extracts, and its DPPH free radical scavenging rate exceeds 90%. This property helps to reduce the damage of oxidative stress to wound tissue and promote the smooth transition of wounds from the inflammatory stage to the proliferation stage.

[0150] 3) Hydrogel has excellent antibacterial and anti-inflammatory effects

[0151] This test case evaluated the antibacterial and anti-inflammatory properties of HA@TA-Okra hydrogel solution;

[0152] Test materials and test methods:

[0153] In a sterile environment, 500 μL of HA@TA, HA@Okra, and HA@TA-Okra hydrogel solutions were added to 24-well plates. The untreated hydrogels served as the control group (HAMA). The surface inoculation concentration of the hydrogel samples in the logarithmic growth phase was 1×10 5CFU / mL (100 μL) of Escherichia coli (E. coli coli) and Staphylococcus aureus (S. aureus) were incubated at 37°C for 4 hours; after incubation, the bacteria were washed with sterile PBS and 100 μL of the wash solution was spread on agar plates; after another 24 hours of incubation at 37°C, bacterial growth was monitored and evaluated.

[0154] The 2',7'-dichlorofluorescein diacetate (DCFH-DA) labeling method was used to study the intracellular ROS levels of RAW264.7 cells to which each group of hydrogel extracts were added under lipopolysaccharide (LPS) stimulation conditions. First, RAW264.7 cells were successfully cultured. Labeling with DCFH-DA enabled intracellular ROS to be converted into substances with fluorescent properties. After RAW264.7 cells were cultured to an appropriate density, they were divided into two groups for treatment. One group of cells was stimulated with LPS to simulate the inflammatory response environment; while the other group of cells, on the basis of LPS stimulation, four different hydrogel extracts were additionally added, and the effect of hydrogels on the intracellular ROS levels of RAW264.7 cells was observed using a fluorescence microscope.

[0155] The concentrations of key inflammatory factors tumor necrosis factor TNF-α, interleukin IL-6, and anti-inflammatory factor IL-10 were quantitatively detected by enzyme-linked immunosorbent assay (ELISA). 5 The cells were uniformly seeded in a 24-well plate at a density of 100 cells / well. Subsequently, the cells were co-incubated with the hydrogel extracts of each group for 24 hours. After the incubation, the supernatant was collected and the dead cells and cell debris were removed by centrifugation. Subsequently, the concentrations of TNF-α, IL-6 and IL-10 were accurately determined using ELISA kits.

[0156] Results and Discussion:

[0157] This test example selected representative Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) as target strains. Figure 3 As shown in A-3D, although pure HAMA hydrogel lacks direct antibacterial activity, its unique three-dimensional network structure acts as a physical barrier to a certain extent, limiting the growth and proliferation of bacteria. After the introduction of sufficient concentration of TA, the antibacterial effect of the hydrogel was significantly improved. HA@TA2.5 hydrogel showed nearly complete inhibition (about 100%) against both test strains, and the effect was comparable to that of the higher concentration HA@TA5 group. Combining cytocompatibility, antibacterial and antioxidant effects, HA@TA2.5 (abbreviated as HA@TA) was screened to maximize the therapeutic effect in practical applications.

[0158] In the present invention, the ROS level in RAW264.7 cells was quantitatively monitored by DCFH-DA fluorescent probe technology. The DCFH-DA probe can penetrate the cell membrane and be oxidized by ROS to generate DCF in the cell. The strong green fluorescence emitted by DCF provides a basis for us to intuitively evaluate the ROS level in the cell. Figure 4 As shown in A-4C, compared with the positive control group, the green fluorescence intensity of the HA@TA-Okra group was significantly reduced (1.29±0.31), which clearly showed that this group exhibited strong antioxidant activity in the intracellular environment. In contrast, the green fluorescence intensity of the HAMA group was significantly higher (33.37±5.56), which reflected that a large amount of ROS was produced in the cells under LPS stimulation, and the HAMA hydrogel did not show obvious inhibitory or scavenging effects on this. It is worth noting that although the ROS levels of the HA@Okra group (14.73±1.69) and the HA@TA group (7.85±1.17) were reduced, they were still higher than the HA@TA-Okra group and lower than the HAMA group. This result shows that both okra extract and TA can enhance the antioxidant activity of HAMA hydrogel to a certain extent, but the antioxidant effect of the HA@TA-Okra group is the most significant.

[0159] In the present invention, the concentrations of TNF-α, IL-6 and IL-10 were quantitatively analyzed by ELISA method. Figure 4 As shown in DF, compared with the LPS and HAMA groups, the experimental groups containing TA and Okra components showed significant advantages in regulating the expression of inflammatory mediators (P<0.001). Specifically, the expression levels of pro-inflammatory cytokines TNF-α and IL-6 of M1 macrophages in these experimental groups decreased significantly, while the secretion of anti-inflammatory cytokine IL-10 of M2 macrophages increased significantly. Among them, the anti-inflammatory effect of the HA@TA-Okra hydrogel group was particularly significant. This phenomenon may be attributed to the synergistic effect of TA and okra components, which enhanced the anti-inflammatory mechanism. The experimental results show that okra extract has potential application value in the field of anti-inflammatory.

[0160] In summary: The HA@TA-Okra hydrogel in the present invention exhibits strong antibacterial and anti-inflammatory capabilities by integrating the unique properties of tannic acid (TA) and okra extract. The experimental results show that the hydrogel can effectively reduce the number of bacteria in the wound site and reduce the inflammatory response, thereby accelerating the wound healing process. Compared with traditional treatment methods, wounds using HA@TA-Okra hydrogel achieved a higher healing rate in a shorter time.

[0161] 4): Hydrogel has good blood compatibility

[0162] This example evaluates the blood compatibility of the HA@TA-Okra hydrogel solution, specifically:

[0163] Test materials and test methods:

[0164] (1) Hemolytic performance test

[0165] Test materials and test methods:

[0166] The hemolytic properties of each group of hydrogels were tested using New Zealand sheep blood. First, the mixed solution of fresh sheep blood and 3.8% sodium citrate (volume ratio of 1:9) was centrifuged (2000rpm, 5min) to effectively separate the red blood cells, and the red blood cells were prepared into a red blood cell suspension with a volume fraction of 5% using physiological saline. Take 0.2g of each group of hydrogels and soak them in 10ml of phosphate buffered saline (PBS) for 48h to obtain extracts of different groups of hydrogels. Then, take out 0.5ml from the extract and add it to a 1.5ml centrifuge tube containing 0.5ml red blood cell suspension for 1 hour of incubation. After the incubation, centrifuge again (2000rpm, 5min) to separate the supernatant. Use an enzyme marker to measure the absorbance value of the supernatant at a wavelength of 540. At the same time, two control experiments were set up: one group used PBS as a negative control (Anc), and the other group used deionized water as a positive control (Apc), and the supernatant (At) was separated from 1 ml of the suspension by centrifugation. The hemolysis rate calculation formula is: Hemolysis rate (%) =

[0167] (At-Anc) / (Apc-Anc)×100%

[0168] Results and discussion: In the present invention, the blood compatibility of the hydrogel was evaluated by the general hemolysis method, and deionized water was set as the positive control group and PBS as the negative control group. Figure 5 As shown in Figures A and 5B, the hemolysis rates of all hydrogel groups were significantly lower than the 5% threshold specified by the ASTM F756-2008 standard. This result confirms that all hydrogels have excellent safety and compatibility in the blood environment.

[0169] (2) Blood coagulation index (BCI)

[0170] Test materials and test methods:

[0171] The blood coagulation performance (BCI) of each group of hydrogels was evaluated by detecting the effects of each group of hydrogels and gauze on blood coagulation. First, each group of hydrogel samples and gauze with a mass of 35 mg were selected, and 100 μL of New Zealand sheep whole blood was dripped onto each of them. Subsequently, incubated at a constant temperature of 37°C for 10 minutes. After the incubation, 10 μL of 0.2M calcium chloride (CaCl2) solution and 10 ml PBS solution were added to each sample. The absorbance value of the PBS solution after blood diffusion was measured at a wavelength of 540 nanometers using a spectrophotometer, recorded as As. At the same time, the absorbance value after only whole blood was added to PBS was measured as a negative control, recorded as Ac. The formula for calculating the coagulation rate is: Coagulation rate (%) =

[0172] As / Ac×100%

[0173] Results and discussion: In the present invention, the hemostatic effect of different groups of hydrogels was verified by coagulation experiments. The blood coagulation index (BCI) is a key indicator for measuring the coagulation effect. The lower the BCI value, the better the coagulation effect.

[35] .like Figure 5 As shown in C and 5D, compared with the gauze group, the BCI values ​​of each hydrogel group were significantly reduced, showing stronger coagulation ability. Among them, the BCI values ​​of the HA@Okra and HA@TA-Okra hydrogel groups were the lowest (21.38% and 21.79%, respectively), and compared with the HAMA group, the coagulation effects of these two groups were better (P<0.05). This shows that the introduction of Okra components may enhance the coagulation performance of hydrogels by promoting the release of coagulation factors, activating platelets, and promoting platelet adhesion.

[0174] (3) Platelet adhesion performance test

[0175] Test materials and test methods:

[0176] Blood cells and platelets were observed by SEM to detect the effects of each group of hydrogels on the adhesion properties of blood cells and platelets. First, each group of hydrogel samples with a mass of 35 mg were selected, placed in a 24-well plate, and a whole blood sponge containing 10% sodium citrate was added. After incubation at a constant temperature of 37°C for 1 hour, all samples were washed 3 times with PBS. All samples were fixed with 4% paraformaldehyde for 2 hours. Subsequently, the samples were dehydrated using an ethanol gradient and observed under a scanning electron microscope.

[0177] Results and discussion: Platelet adhesion performance testing

[0178] The adhesion of blood cells and platelets on the hydrogel surface was directly observed by scanning electron microscopy. Figure 5As shown in Figure E, the SEM image clearly shows that red blood cells and platelets adhere well to the hydrogel surface and their morphology remains normal, which further confirms that the hydrogel has good blood compatibility.

[0179] (4) In vivo hemostatic effect detection

[0180] Liver incision hemostasis effect test

[0181] The hemostatic effect of each group of hydrogels was tested by the SD rat liver incision model. Male SD rats (weight range 200-250 grams) were selected, and the experimental protocol approved by the Ethics Committee of the Army Medical University (AMUWEC20235104) was strictly followed. An untreated control group was also set up. First, the SD rats were anesthetized with sodium pentobarbital, and the fur on the abdomen of the rats was shaved clean and disinfected. A 3 cm incision was made on the left liver lobe of the rat using a scalpel, and bleeding was allowed for 5 seconds. Subsequently, each group of pre-weighed (35 mg) hydrogels was gently covered on the wound, and slight pressure was applied to achieve a hemostatic effect. Record the bleeding time and amount of bleeding.

[0182] Testing of hemostasis effect of tail docking

[0183] Use surgical scissors to cut off the posterior third of the rat's tail. The rest of the procedure is the same as the hemostatic effect test of the liver incision;

[0184] Results and Discussion:

[0185] In the present invention, liver and tail docking models are used. Figure 6 As shown in A-6D, in the liver incision model, the amount of bleeding in the HA@TA-Okra hydrogel group (19±5mg) was significantly lower than that in the other groups, followed by the HAMA group (86±23mg). This result highlights the strong blood absorption capacity of HAMA hydrogel due to its three-dimensional porous structure. It is speculated that okra components may further enhance the coagulation properties of HAMA by increasing the activity of coagulation factors and optimizing platelet function. Further observation Figure 6 B and 6D, in the massive hemorrhage liver incision model, the amount of bleeding in the HAMA group was higher than that in the HA@TA-Okra group (P<0.01). The reason for this is that although the HAMA group has a stable three-dimensional porous structure, in the case of massive bleeding, the structure may have reached a saturated state and could no longer effectively absorb residual blood. In contrast, the HA@TA-Okra hydrogel, by loading okra, enhanced the adhesion of platelets and promoted the formation of platelet thrombi, thereby more effectively sealing the wound and initially achieving a hemostatic effect.

[0186] 5): Hydrogel has the ability to promote cell proliferation and migration

[0187] This test example verifies that the HA@TA-Okra hydrogel solution can promote cell proliferation and migration, specifically:

[0188] (Cytotoxicity and in vitro cell migration behavior of hydrogels.)

[0189] Test materials and test methods:

[0190] The overall proliferation of cells after hydrogel treatment in each group was quantitatively evaluated using the EdU cell proliferation kit. First, L929 cells were cultured: Specifically, under sterile conditions, 100 ul of L929 cell suspension was inoculated into each well of a 24-well cell culture plate, and the cell density of the suspension was adjusted to 2×10^ 5 cells / ml. Subsequently, different types of hydrogel extracts were introduced into each well to stimulate the proliferation response of L929 cells. L929 cells were labeled with EdU. L929 cells were fixed to maintain their morphology and structure, and the fixed cells were systematically stained according to the staining scheme provided by the kit, including incubation with Apollo staining reaction solution and addition of DNA staining solution. Finally, we used an inverted microscope to carefully observe and photograph the stained L929 cells.

[0191] The ability of each group of hydrogels in promoting L929 cell migration was tested by scratch test. First, L929 cells were successfully cultured in a 6-well cell culture plate with 1×10^ 4 L929 cells were inoculated at a density of 10 cells and cultured under appropriate conditions until the cell fusion rate reached about 90% and a uniform cell monolayer was formed. Subsequently, a sterile 200 μl pipette tip was used to accurately scratch a clear and cell-free trace at the bottom of the well plate. After the scratch was completed, the original culture medium was gently discarded, and the well plate was washed with phosphate buffered saline (PBS) to completely remove non-adherent cells and cell debris. Then, HAMA, HA@TA, HA@Okra and HA@TA-Okra hydrogel extracts were added to each well. After incubation in a cell culture incubator for 0 hours (A0, i.e., observation immediately after scratching), 12 hours (As, i.e., observation 24 hours after scratching) and 24 hours (At, i.e., observation 24 hours after scratching), the cells were stained with calcein for 5 minutes. Finally, the migration of L929 was carefully observed and photographed using a fluorescent inverted microscope. The unhealed area after scratching was quantitatively analyzed by ImageJ software, and the scratch healing rate (%) was calculated using the formula. The healing rate calculation formula is: and

[0193] Results and Discussion:

[0194] In the present invention, the effect of hydrogel on cell proliferation was evaluated by EdU cell proliferation kit. Figure 2 As shown in C-2D, the results clearly showed that L929 cells maintained proliferation activity in all test groups. The cell proliferation rate in the HAMA group was the highest, which was attributed to the unique biological function of hyaluronic acid in promoting extracellular matrix remodeling. The proliferation rates of the HA@TA, HA@Okra, and HA@TA-Okra groups were slightly lower than those of the HAMA group, and the differences were not statistically significant, indicating that the introduction of TA and okra did not adversely affect the proliferation ability of L929 cells.

[0195] In the present invention, the hydrogel was tested by a scratch test to evaluate the promoting effect of the hydrogel on the migration of L929 cells. Figure 2 As shown in E-2G, after 12 hours of incubation, the healing rates of the groups showed significant differences. Specifically, the healing rates of the HAMA group, HA@TA group, HA@Okra group and HA@TA-Okra group were 19.95%, 22.36%, 25.46% and 27.93%, respectively, while the control group was only 9.5%. This data shows that compared with the control group, all hydrogel groups showed the effect of promoting cell migration. Further observation of the migration after 24 hours showed that the migration rate of the control group was still significantly lower than that of each hydrogel group. At this time, the wound healing rate of each hydrogel group ranged from 50% to 65%. Although the differences between these hydrogel groups did not reach a statistically significant level, this result still strongly supports the great potential of hydrogel materials in promoting tissue regeneration and wound healing.

[0196] 6) HA@TA-Okra promotes healing of infected wounds

[0197] This test case verifies that the HA@TA-Okra hydrogel solution can promote the healing of infected wounds, specifically:

[0198] Test materials and test methods:

[0199] (1) Full-thickness skin defect model on the back of SD rats

[0200] The effect of each group of hydrogels on wound healing was detected by using a full-thickness skin defect model on the back of SD rats. The specific method is as follows: SD rats (200-250g, male) were selected and randomly divided into 4 groups (n=4), namely the control group (untreated), gauze group, HAMA hydrogel group and HA@TA-Okra hydrogel group. After all rats were anesthetized with sodium pentobarbital and shaved on the back, four wounds with a diameter of about 15mm and a depth of about 2mm were made on their backs using sterile instruments (the four wounds did not interfere with each other). Subsequently, the control group kept the wound untreated; the gauze group covered the wound with gauze; the HAMA hydrogel group and the HA@TA-Okra hydrogel group were evenly coated with 200μL of the corresponding hydrogel until the wound surface was flat. The wound surface was photographed on days 0, 3, 7, 10, and 14, and the changes in the wound area were accurately measured and recorded using Image J software.

[0201] (2) SD rat back infected full-thickness skin defect model

[0202] The same bacterial activation method as in 2.2.10 was used to activate Staphylococcus aureus. In the SD rat back infected full-thickness skin defect model, Staphylococcus aureus (100 μL, 10 6 CFUmL -1 ). The rest is the same as above;

[0203] Results and Discussion:

[0204] In the present invention, the potential of HA@TA-Okra hydrogel in tissue repair was studied by constructing a rat full-thickness skin defect model.

[0205] (1) Hydrogel accelerates the healing of common wounds in rats

[0206] like Figure 7 As shown in A-7H, the HA@TA-Okra hydrogel group exhibited a clear healing process, and the wound area gradually decreased over time. In the early stage of healing (day 7), the wound area of ​​this group was significantly smaller than that of the other groups. By the middle stage of healing (day 14), the hydrogel wound areas of the HA@TA-Okra group and the HAMA group were smaller than those of the control group and the gauze group. HAMA and HA@TA-Okra hydrogels can effectively fill the wound, prevent the invasion of external microorganisms, and accelerate the healing process. It is worth noting that the wound healing effect of the HA@TA-Okra group was statistically different from that of the other three groups (P<0.05), indicating that its wound repair effect was better. Quantitative analysis of wound healing rate ( Figure 7 C) It was further confirmed that HA@TA-Okra hydrogel has significant advantages in accelerating wound repair.

[0207] In the present invention, a full-thickness skin defect model of rats infected with Staphylococcus aureus was constructed to study the tissue repair potential of HA@TA-Okra hydrogel on infected wounds.

[0208] (2) Hydrogel accelerates healing of infected wounds in rats

[0209] like Figure 8 As shown in A-8I, during the treatment period, both the HAMA group and the HA@TA-Okra group significantly promoted wound healing, and the effect of the HA@TA-Okra group was more significant. Especially in the early stage of treatment (day 3), the wound healing rate of the HA@TA-Okra group was as high as 56%, which was much higher than the 20% of the control group (P<0.05) and the 4% of the gauze group (P<0.001). Further analysis of the bacterial activity of the wound on day 3 ( Figure 8 C and D), it was found that the bacterial activity in the HA@TA-Okra group was completely inhibited, while the bacterial activity in the control group and gauze group was close to 100%. The bacterial activity in the HAMA group was also significantly reduced (about 10%), but the effect was not as good as that in the HA@TA-Okra group. This highlights the synergistic antibacterial effect of TA and okra components in the HA@TA-Okra group. As the treatment progressed, the wound healing rate of each group showed an upward trend, but the HA@TA-Okra group always showed the most obvious healing effect. By the 14th day, the wounds in this group were almost completely healed (about 98%), showing its excellent healing ability. The experimental results showed that the HA@TA-Okra hydrogel began to significantly accelerate healing from the 3rd day, and the healing rate on the 10th and 14th days was significantly higher than that of the control group (P<0.05). In contrast, the gauze group had the lowest cure rate throughout the treatment period, which may be related to the fact that gauze as a traditional dressing is prone to wound dehydration and mechanical re-injury.

[0210] Example 3: Application of hydrogel

[0211] The application of the HA@TA-Okra hydrogel solution (Example 1) prepared by the present invention as a wound dressing and hemostatic material is specifically as follows:

[0212] Wound dressing: Cut the prepared HA@TA-Okra hydrogel into appropriate shapes and sizes and directly adhere it to the cleaned wound surface, using its good adhesion and antibacterial and anti-inflammatory properties to promote wound healing.

[0213] Hemostatic material: At the bleeding site, HA@TA-Okra hydrogel is quickly placed on the wound, using its porous structure and excellent water absorption properties to quickly absorb blood, while activating platelets and promoting the coagulation process.

[0214] Example 4: Application of hydrogel

[0215] The HA@TA-Okra hydrogel solution (Example 1) prepared by the present invention is used as a severely infected wound treatment and a tissue engineering scaffold, specifically:

[0216] Treatment of severely infected wounds: For severely infected or difficult-to-heal wounds, HA@TA-Okra hydrogel with a high TA ratio (5w / v%) is used to accelerate the wound healing process by taking advantage of its stronger antibacterial and antioxidant properties.

[0217] Tissue engineering scaffold: HA@TA-Okra hydrogel is used as a tissue engineering scaffold to provide cells with a three-dimensional space that simulates the natural tissue microenvironment, promote cell proliferation and differentiation, and is used to repair damaged tissues.

[0218] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A hydrogel having antibacterial, antioxidant and hemostatic functions, characterized in that: Calculated by mass volume fraction, the natural polymer material is 4%, tannic acid is 1.25-5%, okra is 0.25-2%, and the balance is solvent.

2. The hydrogel having antibacterial, antioxidant and hemostatic functions according to claim 1, characterized in that: The natural polymer material includes one or more of gelatin, chitosan, sodium alginate, collagen, hyaluronic acid, and chondroitin sulfate.

3. The hydrogel having antibacterial, antioxidant and hemostatic functions according to claim 1, characterized in that: The natural polymer material is hyaluronic acid, and the hyaluronic acid is methacrylic anhydride hyaluronic acid; the solvent is a phenyl-2,4,6-trimethylbenzoyl lithium phosphinate solution with a mass concentration of 0.2-1.0%.

4. A method for preparing the hydrogel having antibacterial, antioxidant and hemostatic functions according to claim 1, characterized in that: The steps include: 1) dissolving a natural polymer material in a lithium phenyl-2,4,6-trimethylbenzoylphosphinate solution to form a natural polymer hydrogel precursor solution; 2) dissolving tannic acid and dispersing it into the natural polymer hydrogel precursor solution in step 1) to obtain a natural polymer@tannic acid composite solution; 3) adding okra to the natural polymer @ tannic acid composite solution in step 2) and stirring evenly to obtain a natural polymer @ tannic acid-okra solution; 4) Using UV-crosslinking technology, the natural polymer @ tannic acid-okra solution in step 3) is crosslinked and cured in a mold to obtain a hydrogel with a three-dimensional network structure, that is, a hydrogel with antibacterial, antioxidant and hemostatic functions.

5. Use of the hydrogel having antibacterial, antioxidant and hemostatic functions according to claim 4 in the preparation of healing drugs for treating infected wounds.

6. A use according to claim 5, characterized in that The hydrogel can stop bleeding and promote wound repair.

7. Use of the hydrogel having antibacterial, antioxidant and hemostatic functions according to claim 4 in the field of tissue engineering and regenerative medicine.